2016
DOI: 10.1093/femsec/fiw027
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the effects of ocean acidification on sediment microbial communities in the environment: the importance of ecosystem approaches

Abstract: To understand how ocean acidification (OA) influences sediment microbial communities, naturally CO2-rich sites are increasingly being used as OA analogues. However, the characterization of these naturally CO2-rich sites is often limited to OA-related variables, neglecting additional environmental variables that may confound OA effects. Here, we used an extensive array of sediment and bottom water parameters to evaluate pH effects on sediment microbial communities at hydrothermal CO2 seeps in Papua New Guinea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 71 publications
4
36
0
Order By: Relevance
“…Alpha-Diversity indices were calculated to assess richness and evenness of the microbial communities [25] in the studied samples, based on repeated random subsampling of the amplicon data sets after randomly rarefying the data set to the minimum library size (50517 sequences). Significant differences in alpha-diversity indices between the studied stations were determined by using the non-parametric Kruskal test followed by p-value adjusted Wilcoxon tests [26].…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-Diversity indices were calculated to assess richness and evenness of the microbial communities [25] in the studied samples, based on repeated random subsampling of the amplicon data sets after randomly rarefying the data set to the minimum library size (50517 sequences). Significant differences in alpha-diversity indices between the studied stations were determined by using the non-parametric Kruskal test followed by p-value adjusted Wilcoxon tests [26].…”
Section: Discussionmentioning
confidence: 99%
“…The few studies that have examined the impact of elevated CO 2 on surface sediment community composition have recorded different responses, with some showing no changes to community composition ( Kerfahi et al, 2014 ). A few studies have shown major shifts in the community composition driven by increases to the relative abundance of microphytobenthos ( Tait et al, 2015a ), but the majority of studies have shown only modest changes to community composition ( Tait et al, 2013 , 2015b ; Hassenrück et al, 2016 ). Tait et al (2013 , 2015b ) showed increases to the relative abundance of 16S rRNA sequences affiliated to the Planctomycetacia, again of the Rhodopirellula sp., genera known to be influenced by pH ( Buckley et al, 2006 ; Pollet et al, 2011 ), suggesting a preference of members of this taxa for lower pH environments.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental evidence found ocean warming in isolation, and when combined with low pH, facilitates proliferation of benthic cyanobacteria relative to algal turfs (Ullah et al, 2018). Similarly, a relative increase of mat-forming cyanobacteria within algal turfs under a low pH and high temperature treatment provides further experimental evidence that future ocean conditions may favour benthic cyanobacterial mat expansion (Bender et al, 2014, but see Hassenrück et al, 2016). On the other hand storms, which will also increase in intensity in the coming decades, may dislodge and remove benthic cyanobacterial mats (Becerro et al, 2006).…”
Section: Factors Promoting Cyanobacterial Mat Proliferation On Reefsmentioning
confidence: 97%